1979
DOI: 10.1139/y79-077
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the cardiac inotropic effect of phenylephrine by a tetramine disulfide with irreversible α-adrenoceptor blocking activity

Abstract: The newly synthesized alpha-adrenoceptor blocking drug BHC (N,N'-bis[6-(10-methoxybenzyl-amino)-a-hexyl]cystamine) was found to block irreversibly the positive inotropic effect of the sympathomimetic drug phenylephrine on the isolated rat left atrium. BHC was used to test the adrenoceptor interconversion hypothesis which claims that low temperature converts inotropic beta-adrenoceptors in rat atrium and frog ventricle to alpha-adrenoceptors. There was no evidence of adrenoceptor 'interconversion.' In the rat a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1981
1981
1986
1986

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…We used established techniques for a quantitation of the interaction between atropine-like agents and aadrenoceptor radioligands (Abraham et al, 1981;Cantor et al, 1983) and for estimating the antagonism against phenylephrine on isolated rat aortic strips (Ruffolo et al, 1982;Digges & Summers, 1983) and left atria (Benfey et al, 1979). The K, values for the displacement of [3HJ-WB-4101 binding by atropine and scopolamine determined in the present study are in close agreement with values obtained by others (Cantor et al, 1983).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We used established techniques for a quantitation of the interaction between atropine-like agents and aadrenoceptor radioligands (Abraham et al, 1981;Cantor et al, 1983) and for estimating the antagonism against phenylephrine on isolated rat aortic strips (Ruffolo et al, 1982;Digges & Summers, 1983) and left atria (Benfey et al, 1979). The K, values for the displacement of [3HJ-WB-4101 binding by atropine and scopolamine determined in the present study are in close agreement with values obtained by others (Cantor et al, 1983).…”
Section: Discussionsupporting
confidence: 87%
“…Although rat aorta does contain both a,-and a2-adrenoceptors (Ruffolo et al, 1982), the effects of phenylephrine are almost entirely due to a stimulation of ax1-adrenoceptors (Digges & Summers, 1983). Likewise, phenylephrine has been used as the agonist of choice for a study of a1-adrenoceptormediated effects on the left atria of rats (Benfey et al, 1979). Thus we have confirmed the ax-adrenoceptor blocking properties of atropine and scopolamine (Cantor et al, 1983) and have shown this to be true for anisodamine and anisodine.…”
Section: Discussionmentioning
confidence: 99%
“…Resting diastolic tension was adjusted to give maximal control contractions. Dose-response curves were obtained cumulatively; only one dose-response curve was established in an atrial preparation (Benfey, Yong, Belleau & Melchiorre, 1979). a and f-adrenoceptor assay Membranes of ventricular tissue were prepared by the method of Baker, Boyd & Potter (1980).…”
Section: Inotropic Drug Effectsmentioning
confidence: 99%
“…14 The value of such a model depends as much on the content of structural details testable by future experimentation as on its ability to account for the observed potencies of adenosine analogues. Testing such predictions and comparing receptor subtypes seem a reasonable approach to (10) albumin upon the hydrophobicity of the N6 substituent. The dissociation constant of the analogue albumin complex, K, serves as a measure of binding affinity, and k', which is related to the retention time on a reversed-phase HPLC column, is an index of hydrophobicity.…”
mentioning
confidence: 99%
“…Third, the affinity of the S-3 receptor subregion for a two-carbon fragment is greater than that of the S-l subregion. Thus, A/6-[2(S)-butyl]adenosine (10) is over 3 times more potent than A^-propyladenosine (32), whereas AT6-[2(i? )-butyl]adenosine ( 9) is equipotent with 32.…”
mentioning
confidence: 99%